Materials and design : the art and science of material selection in product design - Ashby, M. F. (Butterworth-Heinemann, 2014)
Materials are the stuff of design. From the very beginning of human history, materials have been taken from the natural world and shaped, modified, and adapted for everything from primitive tools to modern electronics. This renowned book by noted materials engineering author Mike Ashby and industrial designer Kara Johnson explores the role of materials and materials processing in product design, with a particular emphasis on creating both desired aesthetics and functionality. The new edition will feature even more of the highly useful "materials profiles" that give critical design, processing, performance and applications criteria for each material in question. The reader will find information ranging from the generic and commercial names of each material, its physical and mechanical properties, its chemical properties, its common uses, how it is typically made and processed, and even its average price.